Addressing colonial and militarized themes in STEM education - Porter, Sean; Siddiqui, Yusra (Frontiers in Education, 2024)
In response to longstanding inequities and injustices within STEM, this review addresses the pressing need to decolonise STEM education and redefine the purpose of its disciplinary fields. Focusing on the influence of entrenched power structures, particularly the military-industrial complex, this review examines the relatively under-theorised impact of these forces on shaping the goals and scope of certain bodies of STEM education within UK higher education. The first section offers an overview of militarised STEM education and its connections to the challenges of decolonisation. The second section explores strategies and interventions for decolonial pedagogy aimed at challenging discourses and practices that reinforce colonial and militarised narratives within curriculum and teaching. This review highlights how critical pedagogy and Indigenous Knowledge Systems offer educators’ methods to cultivate criticality and humanity in their teaching practices. Ultimately, the review attempts to highlight how STEM education can be re-envisioned to serve broader, more emancipatory, and just purposes. Here the review advocates for a transformative educational paradigm that integrates inclusive pedagogical interventions with critical engagement in the ethical and moral dimensions of STEM practice, with the overarching goal of advancing social justice in teaching practices.